Analysis of Microlearning Effectiveness in Enhancing 21st Century Skills - Rusman Zaenal Abidin (National Dong Hwa University, 2025)
This study examines the effectiveness of microlearning as an innovative educational approach in developing 21st-century skills among students. In the context of rapid globalization and digital transformation, microlearning emerges as a promising solution, offering brief, focused learning materials that are accessible anytime and anywhere through various digital platforms. The research employs empirical evidence from multiple studies to demonstrate that microlearning, particularly through mobile-based and video-based approaches, significantly enhances programming skills, technology acceptance, and digital journalism competencies among learners. The flexible nature of microlearning supports self-paced learning and improves knowledge retention. However, the study also identifies notable limitations in current microlearning material design, especially in developing higher-order thinking skills such as critical thinking in English language learning contexts. The research concludes that while microlearning effectively promotes the development of various 21st-century skills, there remains a crucial need for more comprehensive material development, pedagogical innovation, and varied teaching methods to fully prepare students for the complex challenges of the future workforce and society.